Minimasi Unsafe Action Pada Proyek Pembangunan Mass Rapid Transit (MRT) Phase II Menggunakan Metode Hazard Identification, Risk Assessment, and Risk Control (HIRARC) - Aulia Putri Nurieta; Dian Mardi Safitri; Ika Wahyu Utami (Jurnal Rekayasa Sistem Industri, 2023)
Sumitomo Mitsui Construction Company Utama Indonesia is one of the leading construction companies in Indonesia and is a subsidiary of Sumitomo Mitsui Construction Co., Ltd, based in Japan. Mass Rapid Transit (MRT) is an urban rail-based mode of public service transportation. This research was conducted on the Mass Rapid Transit (MRT) phase II Jakarta construction project in the Glodok - Kota area. Based on observations and interviews, work accidents caused by unsafe actions need to be further identified. This study aims to control the indicators of unsafe actions that can cause work accidents. The method used in this study is Hazard Identification, Risk Assessment, and Risk Control (HIRARC). This research was conducted in several stages, namely identifying the hazard of the unsafe action indicator, conducting a risk assessment of the unsafe action indicator, and determining risk control. The results obtained are based on risk assessment; from the 13 risks, there are 9 types of risk in the low category (low risk), 3 types of risk in the medium category (medium risk), and 1 risk in the high category (high risk). Risk control that can be provided and has been approved by the company is the installation of signs "beware of falling materials", providing external training such as K3 Training for High Building Workers in Lift and Transport Fields, conducting supervision in the work area by increasing the number of supervisory personnel involving supervision and site engineers.